2021
DOI: 10.1007/s10064-021-02312-4
|View full text |Cite
|
Sign up to set email alerts
|

A practical reliability assessment approach and its application for pile-stabilized slopes using FORM and support vector machine

Abstract: Many uncertainties exist in pile-stabilized slopes which make their design substantially complicated. In this paper, a firstorder reliability method (FORM) based on a support vector machine (SVM) and uniform design (UD) is proposed to investigate the reliability of a pile-stabilized slope. A deterministic model considering soil-pile interaction and using a strength reduction method based on the displacement criterion is employed to calculate the factor of safety and the corresponding pile-bending moment. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…FORM is able to consider the effects of random variables' probability distribution types on the β in the sense that the location of MPP differs for different distributions. As illustrated by previous studies [37,39,42,43], FORM is not sensitive to LSF's form. This is because FORM's reliability index is only related to the position of the MMP on the limit-state surface.…”
Section: Formmentioning
confidence: 53%
See 1 more Smart Citation
“…FORM is able to consider the effects of random variables' probability distribution types on the β in the sense that the location of MPP differs for different distributions. As illustrated by previous studies [37,39,42,43], FORM is not sensitive to LSF's form. This is because FORM's reliability index is only related to the position of the MMP on the limit-state surface.…”
Section: Formmentioning
confidence: 53%
“…FORM is another commonly used approximate analytical method in the geotechnical engineering field [7,15,[36][37][38][39]. Low et al [36] applied and compared three constrained optimization FORM procedures in the context of a rock slope and an embankment on soft ground.…”
Section: Formmentioning
confidence: 99%
“…For example, the cohesion usually shows an increasing trend while for internal friction angle a decreasing trend with soil depth due to the increase of confining pressure [38]. Previous research related to the optimal design of anti-slip pile reinforced slopes has shown that the results of slope stability, the evolution of slip surface, and the failure modes considering the friction and cohesion of slope soil as lognormally distributed random variables and the compression strength and pile width as normally distributed random variables are more consistent with the reality compared with the deterministic model [39]. Therefore, a further modification could be focused on the in Supplemental Files or Figure 14 for detailed reinforcement scheme corresponding to scheme number).…”
Section: Limitation Of the Proposed Methodmentioning
confidence: 80%
“…A new multiobjective comprehensive method for improving the performance of antislide piles has been proposed recently: optimizing slope reinforcement using double piles [16][17][18][19]. The reliability of a pile-slope system has also been observed to be generally determined by representative failure modes, which may vary due to pile length, pile spacing, and pile location [20,21].…”
Section: Introductionmentioning
confidence: 99%